Vitamin D and Acute Respiratory Infections—The PODA Trial. (4th September 2019) - Aloia, John F; Islam, Shahidul; Mikhail, Mageda
Abstract: Background: There is considerable heterogeneity in clinical trials examining the role of vitamin D in the prevention of acute respiratory infections (ARIs). Methods: The primary aim of the Physical Performance, Osteoporosis, and Vitamin D in Older African-American Women (PODA) trial was the prevention of bone loss and decline in physical performance. A questionnaire about ARIs was administered every 3 months for 3 years to 260 black American women in a double-blind randomized clinical trial that had a placebo group and a vitamin D supplementation group. The serum 25(OH)D level was maintained >30 ng/mL in the vitamin D group. Results: Serum 25(OH)D was maintained >30 ng/mL in 90% of the active group, whereas levels approximated those associated with the recommended dietary allowance (20 ng/mL) in the placebo group. There was no difference in occurrence of ARIs in the treatment group vs the placebo group. ARIs were not related to total or free 25(OH)D, which were measured at baseline and annually for 36 months. Conclusions: Vitamin D supplementation sufficient to maintain serum 25(OH)D >30 ng/mL does not prevent ARIs in older African American women. ClinicalTrials.gov Registration Number: NCT01153568.